Novel insights into the genetics of smoking behaviour, lung function, and chronic obstructive pulmonary disease (UK BiLEVE): a genetic association study in UK Biobank - Wain, Louise V.; Shrine, Nick; Miller, Suzanne; Jackson, Victoria E.; Ntalla, Ioanna; Artigas, María Soler; Billington, Charlotte K.; Kheirallah, Abdul Kader; Allen, Richard; Cook, James P.; Probert, Kelly; Obeidat, Ma'en; et al. (Elsevier, 2015)
Background